(untitled) (Journal of Management and Social Sciences, 2023)
Despite the fact that access to healthcare services is a prerequisite to good health, rural residents faces variety of barriers in accessing healthcare, due to inadequate health care facilities in the rural areas. However, lack of functional healthcare facility remains the public health concern and this has been one of the factors responsible for high rate maternal mortality which is preventable if the facility is accessible for pregnant women for both ante-natal and post-natal attendance. This study examined the barriers women faced in utilising healthcare facilities. Methodologically, the authors made use of secondary sources of data where relevant empirical literatures were reviewed to assess the barriers in utilization of healthcare facilities in rural areas. The study revealed that many of the healthcare centers, apart from lacking adequate medical personnel, also lack essential drugs and consumables. It was concluded that, to enhance utilization of healthcare services, there must be capacity building and empowerment of people within the community through orientation, mobilization and women empowerment. The study recommended that easy accessibility to healthcare centers by women in rural communities requires strong political will and commitment of the government at all levels.